EUS-FNA Diagnosis with Core Biopsy of Pancreatic Metastases from Primary Breast Cancer - Samuel Galante Romanini; Juan Pablo Román Serrano; Juliana Silveira Lima de Castro; Isabela Trindade Torres; Alex Ingold; André Lucchiari Borini; Luiz Augusto Sanches Zulske; Maria Bruna Feitosa Matias; Jéssica Said de Marchi; José Andrés Sanchez Pulla; José Celso Ardengh (Case Reports in Gastrointestinal Medicine)
Background. The pancreas as a site of metastasis of other primary tumors is a rare event. Pancreatic metastases may occur years after the start of treatment of a neoplasm of another organ or may be the initial manifestation of an unidentified primary tumor. The most commonly reported primary sites for pancreatic metastases are the kidneys, lungs, breast, bowel, and skin (melanoma). Case Summary. The authors report a case of pancreatic metastasis derived from a primary breast cancer that underwent endoscopic ultrasound fine-needle aspiration (EUS-FNA) core biopsy to obtain tissue, which made it possible to perform an immunohistochemical study. Conclusion. We emphasize the importance of outpatient follow-up after the treatment of a neoplasia and the completion of control exams. In addition, we should always be aware of the finding of a secondary lesion in patients who have already been diagnosed with cancer, even if it is located in unusual organs, as in this case, where two metastases of a breast carcinoma to the pancreas were detected.